Investment Property in the Financial Statements of Capital Groups Listed on the Warsaw Stock Exchange - Kwinto, Piotr Prewysz; Voss, Grażyna (European Journal of Economics and Business Studies, 2016)
In recent years, investing in property has become very popular. It is related to a significant decrease in interest rates, which has resulted in a decrease in interest rates on bank deposits and risk-free securities. What is more, this kind of investment seems to be less risky than investing in shares or raw materials due to a steady increase in property prices in Poland in the recent years. Investment property owned by an entity conducting business activity must be properly presented in financial statements, which is next reflected in the evaluation of financial position. Recognition, measurement and presentation of investment property in financial statements have been comprehensively prescribed in International Accounting Standard 40 – Investment Property, which was released in December 2003. It was first applied to financial statements prepared for the reporting period starting after January 1, 2005. The standard was revised twice – first in 2008 and then in 2013. The aim of this paper is to describe the recognition, measurement and disclosure of investment property under polish and international accounting regulations as well as to analyze the presentation of such information in financial statements of the largest companies listed on the Warsaw Stock Exchange. The main methods used include the analysis and evaluation of legal acts and subject-related literature as well as the analysis of information disclosed in financial statements of the largest companies listed on the Warsaw Stock Exchange